Recovering biblical manhood and womanhood : A response to Evangelical feminism - Piper, John, 1946-; Grudem, Wayne A. (Wheaton, Ill. : Crossway Books, 1991)
The past decade has seen the rise of a movement, "evangelical feminism," that has had a profound impact. In Recovering Biblical Manhood and Womanhood, 22 men and women commit their talents to produce the most thorough response yet to evangelical feminism. The book combines systematic argumentation with popular application. It deals with all the main passages of scripture brought forward in this controversy. All who are concerned with the fundamental question of the proper relationship between men and women in home, church, and society will want to read this important and informative book. - Back cover.
Charity, clarity, and hope : the controversy and the cause of Christ (including a response to the statement by Christians for Biblical equality) / John Piper and Wayne Grudem -- The meaning of Kephale ("Head") : a response to recent studies / Wayne Grudem -- The Danvers statement / The council on Biblical Manhood and Womanhood.
Cover title: Recovering biblical manhood & womanhood.
Includes bibliographical references (p. 473-541) and indexes.
Keywords: Sex role -- Religious aspects -- Christianity; Sex role -- Biblical teaching; Men (Christian theology); Women -- Religious aspects -- Christianity; Men (Christian theology) -- Biblical teaching; Women -- Biblical teaching; Men (Christian theology); Men (Christian theology) -- Biblical teaching; Sex role -- Biblical teaching; Sex role -- Religious aspects -- Christianity; Women -- Biblical teaching; Women -- Religious aspects -- Christianity